Do Annual Rings Really Reveal Cd, Ni, and Zn Pollution in the Air Related to Traffic Density? An Example of the Cedar Tree - Cobanoglu, Hatice; Sevik, Hakan; Koç, İsmail (Springer Science and Business Media LLC, 2023)
Heavy metals (HMs) in air pollution seriously threaten the environment. Although plant species are known as good biomonitors, it has not been determined which HM is absorbed by which plant and organs and how much traffic is caused. The objectives are to determine (a) if the HMs examined here are transferred between the annual tree rings and (b) originate from the traffic, and (c) the variation of these HMs' concentrations by wood, outer bark, and inner bark within these organs and density of the traffic. In this study, annual growth rings of Cedrus sp. tree located in Kastamonu city center, Turkiye, were used to determine the variation of cadmium (Cd), nickel (Ni), and zinc (Zn) by organ and traffic density through the last 39 years. As a result, Cd, Ni, and Zn concentrations in outer bark on the roadside were approx. 22.3, 9.6, and 2.5 folds of the concentration in the outer bark on the opposite side. Compared to the values obtained from wood, the concentrations obtained from outer bark were approx. 16.5 folds for Cd, 3.2 folds for Ni, and 5.1 folds for Zn. The results reveal that Cd, Ni, and Zn elements can diffuse into the air due to traffic, their accumulation potential in the cedar tree's woods is relatively high, and their transfer in the wood is limited. In conclusion, the usage potential of this species is high to monitor and reduce the change of Cd, Ni, and Zn in the air from the past to the present.
Keywords: Heavy-Metal Pollution; Pinus-Sylvestris; Bio-Monitor; Plants; Accumulation; Elements; China; Air Pollution; Biomonitor; Cadmium; Heavy Metal; Nickel; Zinc; 13. Climate action; 15. Life on land